Forensic psychiatry, one subspecialty with two ethics? A systematic review - Niveau, Gérard (BMC Med Ethics, 2018)
BACKGROUND: Forensic psychiatry is a particular subspecialty within psychiatry, dedicated in applying psychiatric knowledge and psychiatric training for particular legal purposes. Given that within the scope of forensic psychiatry, a third party usually intervenes in the patient-doctor relationship, an amendment of the traditional ethical principles seems justified. RESULTS: Thus, 47 articles, two book chapters and the guidelines produced by the World Psychiatric Association, the American Association of Psychiatry and the Law, as well as by the Royal Australian and New Zealand College of psychiatrists, were analyzed. The review revealed that the ethics of correctional forensic psychiatry and those of legal forensic psychiatry do not markedly differ from each other, but they are incongruent in terms of implementation. METHODS: In an effort to better understand which ethical principles apply to forensic psychiatry, a chronological review of the literature published from 1950 to 2015 was carried out. CONCLUSION: The ethics of correctional forensic psychiatry are primarily deontological. The principle of justice translates into the principle of health care equivalence, the principle of beneficence into providing the best possible care to patients, and the principle of respect of autonomy into ensuring confidentiality and informed consent. The ethics of legal forensic psychiatry are rather consequentialist. In this latter setting, the principle of justice is mainly characterized by professionalism, the principle of beneficence by objectivity and impartiality, and the principle of respect of autonomy by informed consent. However, these two distinct fields of forensic psychiatry share in common the principle of non maleficence, defined as the non collaboration of the psychiatrist in any activity leading to inhuman and degrading treatment or to the death penalty.